Ejection Fraction from MUGA: Comparisons between Xeleris and Pegasys Workstations - Sasithorn Amnuaywattakorn (2022)
Background: MUGA scans have been well utilized to evaluate left ventricular function, popularly as a non-invasive tool for quantification of left ventricular ejection fraction (LVEF) values. Therefore, it is often requested to periodically evaluate left ventricular function in oncologic patients who are required for cardiotoxic-prone chemotherapy such as Doxorubicin based regimen. Withholding or cessation of the prescribed chemotherapy would be necessary if LVEFs were significantly declined Objective: To correlate individual LVEF values calculating between two different manufacturing workstations. Methods: One-hundred MUGA raw data from oncologic female patients were included. All data were loaded in two different manufacturing workstations, namely Pegasys and Xeleris. LVEF values were subsequently calculated using semi-automated method of gated analysis software in each workstation. The 2 sets of LVEF values were correlated. Results: The agreement between the two workstations was high (r2= 0.93). The differences in LVEF values between two workstations were acceptable (within ± 5%). Conclusions: Our result indicated similarity of LVEF values between two different manufacturing workstations. Therefore, these workstations may be used interchangeably in certain situations.